Efficient group handover authentication for secure 5G-based communications in platoons - Yan, Xiaobei (2023)
In recent years, the world of vehicular communication is in full progress. With the emergence of the fifth-generation (5G) technology, the high bandwidth and low latency features in the 5G vehicle to everything (5G-V2X) network become possible. However, the current 5G mechanism specified by the Third Generation Partnership Project (3GPP) Release 16 incurs high signaling overhead over the radio access network and the core network when a vehicle platoon moves from a source base station to the target base station. Moreover, it also has several security problems in terms of the failure of key forward secrecy (KFS) and lack of mutual authentication. In this paper, we propose an efficient authentication protocol for vehicle platoons in all handover scenarios. By the proposal, the identities of base stations and vehicles are mutually authenticated by certificateless aggregated signatures, which can also reduce signaling overhead and is free from key escrow problems. The proposed protocol has been formally evaluated by BAN-logic and the Scyther tool to show its ability to resist major typical malicious attacks. It has also been analyzed on its security functionality. The performance evaluation demonstrates that the proposed protocol is efficient in terms of signaling, computational and communication cost.